Pengembangan Sistem Pakar Untuk Diagnosa Penyakit Kulit Pada Kucing Berbasis Website Dengan Metode Case Based Reasoning (Studi Kasus: Ummi Pet Care & Pet Shop Balaraja) - Mutiarawati, Raihana; Savitri (CV. Shofanah Media Berkah, 2024)
Current technological developments have advanced rapidly, providing convenience and flexibility in various fields, including human and pet health. Cats, as one of the popular pets, require optimal health care, especially skin health. For this reason, pet care facilities are available to ensure such care. However, cat owners often experience difficulties in checking their cats' health because pet care locations are far away and limited to urban areas. This research aims to develop a website-based expert system that can diagnose cat skin diseases using the Case-Based Reasoning (CBR) method. This method focuses on solving problems by relying on solutions from previous cases. It is hoped that this research will make it easier for cat owners to identify skin diseases and provide useful information regarding their cat's health. The research results show that this system achieves 92% accuracy based on expert assessment. Testing was carried out using black box and white box, and of the 10 cases with 41 symptoms tested, ring worm disease recorded the highest percentage in diagnosis at 83%.